Bee farming system sustainability: An assessment framework in metropolitan France. (November 2019) - Kouchner, Coline; Ferrus, Cécile; Blanchard, Samuel; Decourtye, Axel; Basso, Benjamin; Le Conte, Yves; Tchamitchian, Marc
Abstract: Beekeeping is a long-standing production of livestock, which currently faces several technical and economic challenges such as high colony losses and highly variable honey yields. While the sustainability of current and future bee farms is at stake, the current research on agricultural sustainability assessment poorly considers the technical and management specificities of bee farming systems, systems that remain poorly understood. To fill this gap, we designed a sustainability assessment framework, in other words, a detailed and organised definition of the sustainability of bee farming systems, that identifies the current sustainability issues of these systems at the farm level. Through interviews and workshops, beekeepers and other stakeholders were involved in the design process to include a diversity of viewpoints on the definition of sustainability for bee farming systems, and to ensure the relevance of this assessment framework. The resulting framework highlights the current economic, social and environmental issues of bee farming systems and is organised into six dimensions. Three dimensions are farm-focused, and the three others consider the interactions of the farm with its environment, its territory and the beekeeping sector. That framework reveals the sustainability issues and factors that bee farming systems share with other agricultural sectors as well as their specific issues. In particular, the adaptive capacity of bee farming systems, including their flexibility, their diversity and the learning capacity of the beekeeper, appeared to be a key factor in their sustainability, as is the case for other pastoral systems that have to cope with unpredictable changes in the availability of their feed resources on which they have little direct control. In addition, land management practices partly determine the quality and availability of floral resources, which are hard to estimate, and thus present specific concerns and opportunities in their management. This work provides the first sustainability assessment framework that properly considers the current issues and specificities of bee farming systems, thus providing an outlook on the sustainability challenges of these systems and a basis for the development of an on-farm sustainability assessment tool. Graphical abstract: Unlabelled Image Highlights: A sustainability assessment framework for bee farming systems is provided. Adaptive capacity is a paramount for bee farming systems to face uncertainties. Floral resource quality, access and management are important sustainability issues. Bee farming systems share economic and social issues with other farming systems.